2021
DOI: 10.22376/ijpbs/lpr.2021.11.1.p156-165
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Isoindoline-1,3-Dione Derivatives as Cyclooxygenase (Cox) S Inhibitors

Abstract: Inflammation is the vital part of the immune system's response to injury and infection. It is the body's way of signaling the immune system to heal and repair damaged tissue. The objective of this paper is to design and synthesize a new isoindoline 1,3-dinoe derivative and investigate their selective anti inflammatory activity to COXs. As a potential anti-inflammatory compound, Isoindoline-1,3-dione derivatives were synthesized from the addition reaction of phthalimide, formaldehyde, catalytic amount of potass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…N-alkyl-isoindoline-1,3-diones derivatives showed good inhibitors of the COX enzyme, as did indomethacin and celecoxib [ 18 ]. The presence of the aromatic moiety is important for the affinity for COX2.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…N-alkyl-isoindoline-1,3-diones derivatives showed good inhibitors of the COX enzyme, as did indomethacin and celecoxib [ 18 ]. The presence of the aromatic moiety is important for the affinity for COX2.…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of a nitrogen atom (piperazine ring) into the N-methylphthalimide ligand increases the lipophilicity and affinity for many amino acids of the COX enzyme in both isoforms. In COX-2 molecular docking studies, the new imides showed strong interactions with many amino acids, heralding potential blocking effects for these compounds, but further biological activity studies are needed [ 18 ].…”
Section: Introductionmentioning
confidence: 99%